LAW, WOMEN, AND LITERARY STUDIES: UNDERSTANDING THE THOUGHT OF NAWAL EL-SAADAWI IN WOMAN AT POINT ZERO - Ahmadi, Anas (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2021)
Islamic feminist is currently being discussed, one of which is Nawal E-Saadawi. She is an Islamic feminist who is known for her view on fighting for the fate of women. It is reflected in his non-fiction and literary works. This study aims to explore the view of the feminist writer from Egypt, Nawal El-Saadawi, from a legal context. The research method used in this research is qualitative-interpretative using literary data sources written by Nawal El-Saadawi. The data source used is the novel Woman at Point Zero. The data collection technique was done by using a literature study. The data analysis technique was carried out in two stages: the textual and contextual levels. The result of the research showed that Nawal El-Saadawi's thoughts from her literary context that (1) the law is frightening and unfair in the view of women; (2) men acting on behalf of the law; and (3) women who violate the law.